Uji Sifat Fisikokimia Mocaf (Modified cassava Flour) dan Pati Singkong Termodifikasi untuk Formulasi Tablet - Wira Noviana, Wira Noviana; Halim, Auzal; Lucida, Henny (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
ABSTRACT: Utilization of cassava starch as an excipient in the tablet formulation is still very limited. Various modifications to the cassava starch has been carried out to obtain a better starch properties. The aim of this study was to examine the physi- cochemical properties of MOCAF and modified cassava starch as an excipient for tablet formulation, especially for direct compression method. MOCAF and modified cassava starch is a product of flour and cassava starch is modified mainly by lac- tic acid bacteria (Lactobacillus sp). Then the results of these modifications will be evaluated physicochemical properties, including examination of the surface shape of starch granules using SEM, thermal analysis by DTA, the pattern of starch crys- tallographic by X-ray diffraction, adsorption isotherm, and the content of amylose. The results showed that MOCAF and modified cassava starch granule were rougher- occurred some holes presented distinctively- and more crystalline than Starch 1500. Meanwhile, the result of adsorption isotherms MOCAF and modified cassava starch showed a model type II of adsorption isotherms. Another results show that the amy- lose content of cassava starch modified 48 hours has the highest amylose content that is equal to 33.5714%. Keywords: MOCAF, Modified Cassava Starch, Lactic Acid Bacteria, Tablets ABSTRAK: Penggunaan pati singkong sebagai bahan tambahan dalam formulasi tablet masih sangat terbatas. Berbagai modifikasi terhadap pati singkong telah dilakukan untuk mendapatkan sifat pati yang lebih baik. Tujuan penelitian ini adalah untuk menguji sifat fisikokimia MOCAF dan pati singkong termodifikasi sebagai bahan tambahan dalam formulasi tablet khususnya untuk metoda cetak langsung. MOCAF dan pati singkong termodifikasi merupakan produk tepung dan pati singkong yang dimodifikasi terutama oleh bakteri asam laktat (Lactobacillus sp). Kemudian hasil modifikasi ini akan dievaluasi sifat fisikokimianya, dianta- ranya pemeriksaan bentuk permukaan granula pati menggunakan SEM (Scanning Electron Microscope), analisis panas dengan DTA, pola kristalografi pati dengan difraksi sinar X, adsorpsi isoterm, dan kadar amilosa. Hasilnya menunjukkan bah- wa MOCAF dan pati singkong termodifikasi mengalami perlubangan pada permu- kaan granulanya, dan lebih bersifat kristal jika dibandingkan dengan Starch 1500. Sementara itu, dari hasil pemeriksaan adsorpsi isoterm MOCAF dan pati singkong termodifikasi menunjukkan model adsorpsi isoterm tipe II. Hasil lainnya menun- jukkan bahwa kadar amilosa pati singkong termodifikasi 48 jam mempunyai ka- dar amilosa paling tinggi yaitu sebesar 33,5714%. Kata kunci: MOCAF, Pati Singkong Termodifikasi, Bakteri Asam Laktat, Tablet